Strange Encounter: Depicting An “Other” Reality for Young Readers - YOU Chengcheng (Institut Seni Indonesia Yogyakarta, 2015)
This article explores fantastic encounters between humans and non-humans inChinese and Japanese Children’s literature. Naoko Awa’s collection of short storiesThe Fox’s Window and Other Stories is closely read to elucidate narrative features ofwhat I call as “strange encounter”, the magic realistic human-animal encounter inChinese and Japanese cultural context. Chinese supernatural literature and culturaltradition of yaoguai, which have been assimilated into Japanese culture (Japaneseyōkai), are referred to throughout my discussion. Todorov’s approach to thefantastic, Judith Zeitlin’s study of Strange Tales of Liaozhai Studio, and RosemaryJackson’s study of fantasy are drawn upon to illuminate the meaning of encountersbetween men and animals. I argue that magic realism as a relatively new genrefor young readers, not only reflects the author’s individual creative experienceof the fantastic but also partakes in the sense of an “other” reality that resonatesthroughout a cultural community.Perjumpaan Ganjil: Gambaran suatu Realitas “Liyan” bagi Pembaca Muda.Artikel ini membahas perjumpaan fantastis antara ‘manusia’ dan ‘non-manusia’ didalam sastra anak Cina dan Jepang. Antologi cerita pendek karangan Naoko Awa TheFox’s Window and Other Stories akan dikupas untuk memaparkan fitur naratif yangdisebut sebagai ‘perjumpaan aneh’ (strange encounter), perjumpaan magis-realis antaramanusia dengan binatang dalam konteks kebudayaan Cina dan Jepang. Karya sastrasupernatural Cina dan keberadaan yaoguai yang telah diasimilasi dalam kebudayaanJepang (disebut youkai) menjadi sebuah referensi penting dalam artikel ini. Pendekatanfantasi dari Todorov, studi Judith Zeitlin tentang Strange Tales of Liaozhai Studio,dan studi fantasi dari Rosemary Jackson digunakan untuk memperjelas arti dariperjumpaan antara manusia dan binatang. Magis-realis sebagai sesuatu yang baru bagi pembaca muda tidak hanya merefleksikan pengalaman kreatif pribadi sang pengarang akan fantasi, tetapi juga berperan dalam pembentukan realitas “liyan” dalam sebuahkomunitas budaya.